Description of The Level of Knowledge About Covid-19 Vaccines Among Adolescents In Public Junior High Schools - Bagus Putro Pamungkas; Noerma Shovie Rizqiea; Erlina Windyastuti (Adi Husada Nursing Journal, 2023)
Coronavirus Disease 2019 (Covid-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). SARS-CoV-2 is a novel coronavirus that had not been identified in humans before. There are at least two known types of coronaviruses that can cause severe illnesses, such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). One of the measures to break the chain of Covid-19 transmission is through Covid-19 vaccination. The purpose of this study is to determine the characteristics of respondents and the overview of the level of knowledge about the Covid-19 vaccine among teenagers at Junior High School 1 Andong. This research is descriptive in nature. The population of this study consists of students of Junior High School 1 Andong, in grade 7 and 8, academic year 2020/2021, totaling 458 students. The sample calculation using the Slovin formula resulted in 82 respondents. The sampling was conducted using probability sampling techniques with cluster sampling. Data collection was performed using a questionnaire on knowledge about Covid-19 vaccines and national Covid-19 vaccination, taken from previous research. The characteristics of the respondents showed that the majority were early teenagers aged 11-13 years, totaling 66 respondents (80.5%), and mostly female, totaling 44 respondents (53.7%). The level of knowledge about Covid-19 vaccines among teenagers in Junior High School 1 Andong is mostly sufficient, with 74 respondents (90.2%). From these results, it can be concluded that the low knowledge of teenagers about Covid-19 vaccines is influenced by irresponsible information circulating about the vaccines. The more information teenagers receive about Covid-19 vaccines, the better their knowledge becomes.